2020
DOI: 10.1098/rspb.2020.0668
|View full text |Cite
|
Sign up to set email alerts
|

The development of flight behaviours in birds

Abstract: Flight is a unique adaptation at the core of many behaviours in most bird species, whether it be foraging, migration or breeding. Birds have developed a wide diversity of flight modes (e.g. flapping, gliding, soaring, hovering) which involves very specialized behaviours. A key issue when studying flight behaviours is to understand how they develop through all the ontogenetic stages of birds, from the embryo to the flying adult. This question typically involves classical debates on animal behaviour about the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 86 publications
(106 reference statements)
3
15
0
Order By: Relevance
“…Overall, changes in the share of time spent on each behavior throughout the PFDP were more gradual and occurred later in reintroduced individuals than in wild ones. This progressiveness on the percentage of each movement observed in all individuals and its delay is consistent with the development of ight skills, in which ights that involve apping (i.e., searching/foraging) are rstly acquired and perfectioned with practice, and more complex movements (i.e., active hunting and travelling/relocating) are later developed (Ruaux et al 2020). In the Golden eagle, at the beginning of the dependence period, apping ights were found, and complex movements developed later (Walker 2008), indeed, Weston et al (2018) showed that the PFDP could be divided into two phases: ontogenic phase and maintained phase.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Overall, changes in the share of time spent on each behavior throughout the PFDP were more gradual and occurred later in reintroduced individuals than in wild ones. This progressiveness on the percentage of each movement observed in all individuals and its delay is consistent with the development of ight skills, in which ights that involve apping (i.e., searching/foraging) are rstly acquired and perfectioned with practice, and more complex movements (i.e., active hunting and travelling/relocating) are later developed (Ruaux et al 2020). In the Golden eagle, at the beginning of the dependence period, apping ights were found, and complex movements developed later (Walker 2008), indeed, Weston et al (2018) showed that the PFDP could be divided into two phases: ontogenic phase and maintained phase.…”
Section: Discussionsupporting
confidence: 74%
“…During the ontogenic phase, eagles rst increase their mobility, during the rst 10 weeks (68 days), and later, this mobility was maintained until week 14 (99 days). However, the ability to perform complex movements seems to be acquired sooner if there is parental presence (Ruaux et al 2020). Juveniles learning from parents has also been observed in the Osprey (Pandion haliaaetus), where hand-raised chicks acquired hunting skills without the presence of other conspeci cs (Schaadt and Rymon 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies demonstrated that bats' and birds' have separate evolutionary origins, they share aerial mobility, smaller body weight and brain size, and differential adaptative phenotype responses for flying (33)(34)(35)(36). In contrast to birds and bats, mice do not need to meet the weight and volume constrains imposed by flying (37,38).…”
Section: Morphological Diversity Of Surveillant Microglia Across Species Under Homeostatic Conditionsmentioning
confidence: 93%
“…In addition to reflexes, neonatal birds and mammals have some very elementary action patterns (motor programs), so much so that during their implementation the cerebellum has to rectify and organize the motor sequences that compose them in order to adapt them to the environment [37]. For example, the flight of birds is due to the development of ontogenetic processes and motor learning [38].…”
Section: The Actionsmentioning
confidence: 99%